IDEAS OF NATIONAL AWAKENING AND THE RESTORATION OF CULTURAL IDENTITY IN THE WORKS OF ABDURAUF FITRAT - Shahrizoda Shuhratbek qizi Abdufattayeva (Western European Studies, 2025)
This article analyzes the socio-political and intellectual ideas of Abdurauf Fitrat, one of the leading representatives of the Jadid movement in early twentieth-century Turkestan, with particular emphasis on the concepts of national awakening and the restoration of cultural identity. Using textual and historical analysis, the study examines Fitrat’s major works, including “Munozara”, “Bayonoti Sayyohi Hindi”, and “Rahbari Najot”, to demonstrate how enlightenment, language reform, historical memory, and cultural unity constitute the core elements of his national thought. The article argues that Fitrat understood national awakening not merely as a political struggle, but as a comprehensive cultural and intellectual process aimed at overcoming colonial domination and social stagnation. By situating Fitrat’s ideas within the broader context of Muslim reformism and colonial modernity, the study highlights his decisive role in shaping the ideological foundations of the Turkestan national liberation movement and the formation of modern Uzbek national identity.
Keywords: Fitrat; “Debate”; Statement of the Indian Traveler